The Mission of the Teacher of the Higher School as the Scientist, Instructor and Person - V I Kazarenkov (Peoples' Friendship University of Russia (RUDN University), 2008)
The article considers the teacher of the higher school as the subject of the educational process within the framework of which the teacher aspires to use the opportunities for an all-round development and self-improvement, to be really able to help the student as the scientist, instructor and person.